Prasasti Plosorejo sebagai Data Baru Masa Sindok dalam Sejarah Indonesia Kuno: Kajian Struktur dan Penanggalan: Prasasti Plosorejo sebagai Data Baru Masa Sindok dalam Sejarah Indonesia Kuno: Kajian Struktur dan Penanggalan - Ocsanda, Devina (BRIN, 2024)
The Plosorejo inscription, which has been established as a cultural heritage at the district/city level, has not yet been published in its complete edition. The research on Plosorejo Inscription resulted several new findings that can contribute to the addition of data in ancient Indonesian history. This research is an epigraphic research or text-aided archaeology with text as the main focus to reconstruct ancient Indonesian history. This paper presents the results of script translation, structure analysis, and dating analysis. The result of this research shows that Plosorejo Inscription has two parts, which are Plosorejo A and B Inscriptions. The structure of the inscription shows an indication that the inscription has two dates that begin two different decrees regarding sīma that are interrelated. The date that is still legible in the Plosorejo inscription, 852 Ś/930 AD, is the date that begins the Plosorejo B inscription. The inscription was published in that year or even earlier. Based on the dating component, the figure of Sri Maharaja whose name is no longer legible refers to Siṇḍok. Therefore, the Plosorejo Inscription can be placed to the early inscriptions of the Siṇḍok Period